On economic paradigms - McCombie, John S. L. (Revista Economia & Gestão, 2008)
Is there progress in economics and, if so, how can we be certain? This may seem a strange question. After all, one has only to compare articles in any leading economics journal today (say, the Economic Journal) with those in the same journal fifty years ago to see a radical change. Sophisticated mathematical modelling and econometric testing using large data sets are now commonplace in modern economics articles: yet half a century ago most articles were verbal and statistical testing rudimentary.1,2 However, advances in technique should not be confused with improvements in understanding.